2020
DOI: 10.3389/fpsyg.2020.550219
|View full text |Cite
|
Sign up to set email alerts
|

Positive Influence of Role Ambiguity on JD-R Motivational Process: The Moderating Effect of Performance Recognition

Abstract: Most previous research has shown the negative influence of role ambiguity on employes' motivational process. This has led to role ambiguity being perceived as a main hindrance demand in the workplace, with a negative effect on the Job Demands Resources (JD-R) model's motivational process. Recent theories propose that job demands can be perceived by employes as a challenge, rather than a hindrance. However, there is little evidence on which elements of the organizational context shape this perception. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…To date, role ambiguity has been one of the most studied job demands, producing significant negative consequences in the work context [2,8,20]. However, a relevant contribution to the knowledge of the current study is that the demands are transformed depending on contextual factors in the public administration.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
See 2 more Smart Citations
“…To date, role ambiguity has been one of the most studied job demands, producing significant negative consequences in the work context [2,8,20]. However, a relevant contribution to the knowledge of the current study is that the demands are transformed depending on contextual factors in the public administration.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
“…It has been pointed out that role ambiguity plays an essential role in extra-role performance behavior [53]. Some studies have shown that employees will carry out more voluntary behaviors after receiving support from the leader in highly ambiguous situations [2,29,54]. This exposes that employees in ambiguous contexts will put more effort at work and perform behaviors beyond what is formally established when there are supportive behaviors [55].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot exclude the possibility that performance recognition changes the effect of RA on engagement from negative to positive, as suggested by a recent study. 33 Lastly, we did not control for potential attrition biases; participants with higher levels of psychological illbeing may have more likely dropped from the survey.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the role behavior model showed role congruence with others’ expectations and self-expectation. Martínez-Díaz et al (2020) pointed out that role expectation is the public expectation of the behavior of a person with a specific social status. This also includes self-expectation and public expectation of the role.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%